Comparative Study of Radiation Exposure of Patients undergoing Transradial and Transfemoral Coronary Angiogram and Percutaneous Coronary Intervention - Mazumder, Forhad Karim; Mahmood, Khaled; Md Jafar, Abul Hasnat; Hoq, Enamul; Sharmin, Rubaba (Medicine Today, 2022)
Introduction: Coronary artery disease (CAD) is now the leading cause of death worldwide. Percutaneous coronary interventions (PCIs) are an important group of technologies for the diagnosis and treatment of patients with CAD. PCI is usually performed using the transfemoral (TF) approach but the transradial (TR) approach has been increasingly used as an alternative to TF approach due to less vascular complications, earlier ambulation and improved patient comfort. Accurate assessment of radiation exposure during PCI is paramount important as radiation has many short and long term hazards. TR and TF route has distinct advantages and disadvantages. But in respect of radiation exposure of patients there are controversial evidence between TR and TF approach. Objective: To compare the radiation Exposure in patients with percutaneous coronary intervention by TR and TF approach. Materials and Methods: This prospective observational comparative study was conducted in the National Institute of Cardiovascular Diseases, Dhaka, from June 2015 to May 2016. A total of 200 patients were selected and categorized into two groups (Group I= Trans radial, n =100) and (Group II = Trans femoral, n= 100). Again divided into subgroups (group Ia, trans radial CAG = 70, group IIa, trans radial PCI =30) and (group IIa, trans femoral CAG =70, group IIb, trans femoral PCI = 30). Then different outcome variables were evaluated and compared. Results: Patient demographics were the same in both groups. Fluoroscopy time during TR and TFCAG and PCI was (4.4.±1.6 min vs 4.1±3.9 min, p=0.61) and (11.7±1.3 min vs 11.1±1.5 min, p=0.13) respectively. Regarding radiation dose during TR and TF coronary angiogram, Dose area product(DAP) were (2732±1195.5 mGym2vs 2434±488.0 mGym2, p=0.07&) and Air Kerma (AK) were (307.6 ±112.2 mGy vs 283.7±48.5 mGy, p=.10) with statistically no significant difference of radiation dose (DAP and AK) between two groups. Utilization of Contrast volume during TR and TF angiogram (64.8±8.9 vs 68.2±7.5, p=0.01) were less in trans radial group. Also Utilization of Contrast volume in TR-PCI and TF- PCI (168.0±13.0 vs 177.7±19.9 ml ,p=0.03) were less in trans radial PCI. Conclusion: The basis of the results, no significant differences were found in patient of radiation dose in both TR and TF group. Furthermore utilization of contrast volume was lower in trans-radial CAG and PCI. Trans radial CAG and PCI can be performed with the same safety as for the trans femoral approach. Medicine Today 2022 Vol.34(2): 130-135